Disposition kinetics, urinary excretion and dosage regimen of meloxicam in crossbred calves after single subcutaneous injection - DUMKA, V K; SRIVASTAVA, A K (The Indian Journal of Animal Sciences, 2014)
The disposition kinetics, urinary excretion and dosage regimen of meloxicam were investigated in crossbred calves following its single subcutaneous administration of 0.5 mg.kg-1. The peak plasma drug concentration was attained at 6 hr and the minimum therapeutic plasma concentration was maintained from 0.5 to 48 hr of administration. The absorption half-life, apparent volume of distribution and area under the plasma concentration-time curve were 1.45±0.1 hr,0.09±0.002 L.kg-1 and 208.9±2.81 µg. ml-1 hr respectively. The elimination half-life and total body clearance were 24.7±0.66 hr and 2.4±0.03 ml.kg-1. hr-1 respectively. About 3% of the total administered drug was excreted in urine within 24 hr. On the basis of disposition kinetic parameters obtained in the present study, a satisfactory subcutaneous dosage regimen of meloxicam in cattle was calculated to be 0.55 mg.kg-1 followed by 0.4 mg.kg-1 at 48 hr interval.